The impact of the gospel on the adivasis of south Gujarat an investigation into the mission methods - Dasan, Ebenezer D. (Bangalore Centre for Contemporary Christianity, 2009)
Study conducted among the Kukna, Gamit and Vasava adivasis of south Gujarat, India
Originally presented as the author's thesis (Ph. D.)--Consortium for Indian Missiological Education, 2006. - Includes bibliographical references (p. [346]-372)
Zugl.: Bangalore, Consortium for Indian Missiological Education, Diss., 2006
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Missions -- India -- Gujarat; Adivasis -- Religion -- India -- Gujarat; Christianity -- India -- Gujarat; Gujarat (India) -- Religion; Hochschulschrift